Policy and planning - MOTEN, Fred (Institutional Knowledge at Singapore Management University, 2009)
Policy is the imposition of insecurity, the oppressive regulation of the plans and operations by which the objects of policy anticipate and object to policy. These are notes toward an understanding of policy that also take up the question of whether it is inevitable that hope, and being wary of false hope, turn to policy. We suggest that ongoing operations and plans must be seen in fugitive opposition to the widespread attempts to formulate and participate in something called policy.